Parental job loss and infant health - Jason M. Lindo (Institute for the Study of Labor (IZA), 2010)
Although there exists a large literature documenting various consequences of job loss, this paper is the first to explore the extent to which the health effects of job displacement extend to the children of displaced workers and also the first to consider whether there are any harmful effects for children who are not yet born when the separation occurs. I use detailed work and fertility histories from the Panel Study of Income Dynamics to estimate the effect of parents' job displacements on children's birth weights. These data allow for an identification strategy that essentially compares the outcomes of children born after a displacement to the outcomes of their siblings born before using mother fixed effects. I find that husbands' job losses have significant negative effects on infant health. They reduce birth weights by approximately four and a half percent with suggestive evidence that the effect is concentrated on the lower half of the birth weight distribution.
Keywords: I10; J13; J63; 330; children; infant health; job loss; displacement; Eltern; Arbeitslosigkeit; Kinder; Gesundheit; Schätzung; USA